3021 Strengthening Translational Research Through Citizen Scientist Education - Brishke, Janet (J Clin Transl Sci, 2019)
OBJECTIVES/SPECIFIC AIMS: This project aimed to offer Citizen Scientists basic knowledge about clinical and translational research, as well as introductory information to the topics a Citizen Scientist may work with at the University of Florida (UF). As part of that goal, several objectives were identified: (1) create a curriculum to operationalize training for new Citizen Scientists, (2) utilize best practices in educational research for curriculum design and implementation, (3) create a resource that can be freely available to other groups, and (4) implement the finished curriculum with Citizen Scientists at UF. METHODS/STUDY POPULATION: Working with an expert in the field of instructional design, an overall design plan was created and implemented. This included first conducting interviews with Citizen Scientists to determine the most appropriate format for the content, creating 10-minute videos with subject matter experts, and crafting learning assessments for each didactic video. Topics for the curriculum were conceptualized by gathering input from CTSI leaders, Citizen Scientists, and staff members, and learning objectives were created to help guide the content creation. The ADDIE (Analysis, Design, Development, Implementation, Evaluation) instructional design model was utilized to help guide the creation process, and this included a formative evaluation of the content, where assessment questions or videos were edited in response to Citizen Scientist feedback. It was important to both CTSI leadership and the Citizen Scientists themselves that the curriculum be widely accessible, so the curriculum was made as an open educational resource, meaning that it is available online for use by anyone with content that can be customized to specific programs or organizations. To implement the curriculum with UF Citizen Scientists, the materials were ported into Canvas, a widely utilized learning management system at UF. Participants were split into two groups, one group with Citizen Scientists already in the program (n=6) and a group with new Citizen Scientists (n=2). IRB approval to conduct this pilot test and share the results was obtained, and implementation ran from July 2017- January 2018. RESULTS/ANTICIPATED RESULTS: Data were taken from participant scores on the curriculum’s 15 didactic learning assessments, and while the number of attempts on assessments was not limited, only first-attempt results were analyzed. Veteran Citizen Scientists scored higher than the new Citizen Scientists, with an overall score across all assessments of 84% vs 74%. The existing Citizen Scientists performed better on most topics, however the newer Citizen Scientists outscored the veterans on two modules: Cultural Competency (90% vs 77%) and Biomedical Informatics and Big Data (80% vs 73%). The newer members also had fewer retakes on these two modules, with the newer members having only one retake for these two modules, compared to seven total retakes across both modules for the established members. Participants were also asked basic questions about learning comprehension, video quality, and assessment item clarity, in addition to offering narrative feedback. Participants across both groups seemed largely pleased with the curriculum, as indicated by results of the course evaluation. Most (75%) Citizen Scientists felt it was easy to understand the information in the video tutorials, while 75% of Citizen Scientists felt that the assessment items were comprehensive, and 62.50% felt that the assessment items matched the learning objectives. The new Citizen Scientists were far more likely to respond favorably to the video and assessment evaluation questions, with 95% of all responses marked as “agree” or “strongly agree”, compared to 57% of the responses from the established Citizen Scientists. DISCUSSION/SIGNIFICANCE OF IMPACT: The performance of new vs veteran Citizen Scientists underscores the need for introductory information on clinical research topics for new community stakeholders, as well as the need for ongoing refresher training. Though the existing Citizen Scientists had been working with these topics already, and some had experienced the modules already through the formative evaluation, some topics remained a challenge for participants, a notion reflected in their assessment scores. Clinical research, particularly translational research, can be difficult to understand, and when a stakeholder understands the fundamentals underlying the research with which they are assisting, communication barriers are eliminated, feedback is well-reasoned and actionable, and there is greater buy-in from stakeholders. Understanding the clinical research process helps community stakeholders better understand their contribution to research and offer critical feedback to aid in implementation of research findings in health-related settings.